Long COVID: Association of fear and loneliness with anxiety, depression, and post-traumatic stress disorder: A case-control study - Aceituno, Héctor; Barrancas, Andrea; Quiroz-Bravo, Fernando; Rigaud, Dairene; Pérez-Cuesta, Denis; Osores-Espinoza, Marcela; Rojas-Catejo, Catalina; Khan, Abid; Figueroa-Torres, Carla; Tobar-Bustamente, Aline; de la Cruz, José Gutiérrez; Burgos-Alarcón, Francisca; et al. (Gaceta Médica de Caracas, 2024)
Introduction: Illness-related fear has emerged as a unique mental health concern for individuals with long-standing COVID-19. Our research examined the interplay between fear, feelings of loneliness, depression, anxiety, and post-traumatic stress disorder (PTSD) among COVID-19 patients.